AN ANALYSIS OF TOPICS AND SPEECH FEATURES IN THE ACTIVITY OF GOSSIPING BY FEMALE PARTICIPANTS IN INTERMEDIATE LEVEL OF SANTHI BUDAYA ART FOUNDATION NORTH BALI IN YEAR 2014/2015 - ., I Gusti Made Gari Mahardika; ., Prof. Dr.I Ketut Seken,MA; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menganalisis pembicaraan tentang fitur-fitur sosiolinguistik dan topik gosip yang digunakan oleh wanita dalam kehidupan sehari-hari. Objek dari penelitian ini adalah perempuan-perempuan yang tergabung dalam komunitas Santhi Budaya, umur 14-17 tahun. Penelitian ini menggunakan pendekatan kualitatif dengan desain multiple-case yang memungkinkan peneliti untuk mengkaji fenomena dalam penelitian. Terdapat 13 percakapan yang dianalisis dalam penelitian ini. Hasil penelitian ini menunjukkan: partisipan perempuan di Santhi Budaya menggunakan empat kategori gossip, yaitu: house-talk, scandal, bitching, dan chatting. Sementara itu, dari 10 fitur-fitur pembicaraan yang diajukan dalam penelitian ini, hanya lima yang muncul dalam data, diantaranya lexical hedges, intensifiers, tag question dan swear words. Semua topik itu muncul 21 kali dari 13 percakapan dan fitur-fitur pembicaraan muncul 99 kali. Dari hasil penelitian ini, dapat dikatakan jika partisipan dari percakapan ini cenderung mengganti topik dari satu ke yang lainnya ketika mereka bergosip.Kata Kunci : Fitur berbicara, gosip, topik, wanita This study aimed at analyzing speech in terms of sociolinguistic features and topics of gossiping which are usually shared by female participants in their daily conversations. The objects of this study were the female participants of Santhi Budaya, age 14-17 years in the intermediate level. This study used a qualitative approach and the design used multiple-case study which allowed the researcher to explore the phenomena under study. There were 13 conversations analyzed in this study. The findings showed that: The female participants of Santhi Budaya applied four categories of gossip, namely; house-talk, scandal, bitching and chatting. On the other side, from ten speech features proposed in this study, only five emerged in data. They are Lexical hedges, intensifiers, tag question, question intonation and swear words. All those topics emerged 21 times from 13 conversations and the speech features emerged 99 times. From these findings, it could be ascertained that the participants of the conversations occasionally tended to switch the topic from one to another while they were gossiping and more frequent a topic emerges in a conversation, the higher its chances of having various speech features.keyword : Female, Gossiping, Speech Features, Topics